Serotypes of Streptococcus pneumoniae Isolates from Children with Invasive Pneumococcal Disease in Turkey: Baseline Evaluation of the Introduction of the Pneumococcal Conjugate Vaccine Nationwide - Ceyhan, Mehmet; Gurler, Nezahat; Yaman, Akgun; Ozturk, Candan; Oksuz, Lutfiye; Ozkan, Sengul; Kizirgil, Ahmet (Amer Soc Microbiology, 2011)
Before use of the pneumococcal conjugate vaccine PCV7 became widespread in Turkey, 202 invasive pneumococcus isolates were analyzed. The most common serotypes were 19F and 6B. In children <= 2 years of age, the potential coverage rate of PCV7 was 69.5%. The most frequent non-PCV7 serotypes were 19A, 3, 1, 6A, and 8.
Keywords: Childhood Immunization; Resistance; Region; 19A